2019
DOI: 10.1124/dmd.118.084210
|View full text |Cite
|
Sign up to set email alerts
|

Brain Distribution of a Panel of Epidermal Growth Factor Receptor Inhibitors Using Cassette Dosing in Wild-Type and Abcb1/Abcg2-Deficient Mice

Abstract: Tyrosine kinase inhibitors that target the epidermal growth factor receptor (EGFR) have had success in treating EGFR-positive tumors, including non-small-cell lung cancer (NSCLC). However, developing EGFR inhibitors that can be delivered to the brain remains a challenge. To identify optimal compounds for brain delivery, eight EGFR inhibitors [afatinib, 6-[4-[(4-ethylpiperazin-and vandetanib] were evaluated for distributional kinetics using cassette dosing with the ultimate goal of understanding the brain penet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 56 publications
(55 reference statements)
2
36
0
Order By: Relevance
“…One currently accepted way to define physicochemical properties is by using a weighted scoring approach, known as the Central Nervous System – Multiparameter Optimization (CNS-MPO) 5153 . The CNS-MPO algorithm uses a weighted scoring function that assesses 6 key physicochemical properties (clogP, clogD, MW, TPSA, HBD, and pKa) that indicate relative BBB penetration.…”
Section: Results and Discussonmentioning
confidence: 99%
“…One currently accepted way to define physicochemical properties is by using a weighted scoring approach, known as the Central Nervous System – Multiparameter Optimization (CNS-MPO) 5153 . The CNS-MPO algorithm uses a weighted scoring function that assesses 6 key physicochemical properties (clogP, clogD, MW, TPSA, HBD, and pKa) that indicate relative BBB penetration.…”
Section: Results and Discussonmentioning
confidence: 99%
“…The ALTER0303 study also showed that anlotinib can prolong PFS in lung cancer patients with BM (30). However, no preclinical study has shown that anlotinib can cross the BBB (18). The detailed mechanism of anlotinib action in lung cancer patients with BM should be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with the EGFR T790M mutation, the distribution of osimertinib (AZD9291) in brain tissue was signi cantly higher than that of the rst and second generation EGFR/ALK-TKIs (17,18). AURA3 trial was a phase III clinical study, which tested AZD9291 (80 mg/d) vs standard dual drug chemotherapy (containing platinum), and found that AZD9291 signi cantly prolonged PFS (mPFS: 11.7 vs 5.6 months; hazard ratio [HR] 0.32, 95% con dence interval [CI] 0.15-0.69; p = 0.004), with objective response rate (ORR) of the central nervous system of 70% vs 31% for AZD9291 treatment vs standard dual drug chemotherapy, respectively (19).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, previous attempts targeting EGFR in GBM have not been successful and may be a result of the diverse molecular features of the molecule [ 163 ]. In addition, Kwatra and colleagues [ 164 ] outlined the major flaws of failed clinical trials with first- and second-generation EGFR tyrosine kinase inhibitors (EGFR-TKIs): (i) EGFR-TKI gefitinib blocks the cell-surface receptor but does not abrogate downstream signaling, promoting alternate tumor growth signaling pathways; (ii) Failed clinical trials included both wild-type and EGFR-activated GBM patients instead of patients with activated EGFR or EGFR vIII ; and (iii) Most EGFR-TKIs (e.g., erlotinib, gefitinib, afatinib, and lapatinib) are poorly penetrant to the brain [ 165 ]. However, a third-generation EGFR-TKI, AZD9291, has recently been approved for the treatment of non-small cell lung cancer, irreversibly binds with high affinity to EGFR vIII , and is ~10 times more efficient than first-generation EGFR inhibitors in inhibiting tumor cell proliferation in an orthotopic GBM model [ 166 ].…”
Section: Treatments In Developmentmentioning
confidence: 99%